A SISTEM PAKAR DIAGNOSIS PENYAKIT PADA PEROKOK PASIF DENGAN METODE CERTAINTY FACTOR - Adipamungkas, Bayu Satria; Sahputra, Eka (UNIVED Press, 2021)
The adverse effects of cigarette smoke generally vary, depending on the age and condition of people who become passive smokers, including the impact of cigarette smoke on adults and the impact of cigarette smoke on pregnant women. If the impact of cigarette smoke on adults often inhale cigarette smoke, it can increase the risk of developing lung cancer by 20-30%. An expert system is a system that uses human knowledge where the knowledge is entered into a computer and then used to solve problems that usually require human expertise or expertise. How to make an expert system application for disease diagnosis in passive smokers with the certainty factor method. Can apply the certainty factor method rule pattern on the application of an expert system for diagnosis of disease in passive smokers. It is hoped that the development of this application can be a reference not only for passive smoking so that it is useful for the development of information technology.